ASME 2010 Internal Combustion Engine Division Fall Technical Conference 2010
DOI: 10.1115/icef2010-35058
|View full text |Cite
|
Sign up to set email alerts
|

On Comparative Performance Testing of Prechamber and Open Chamber Laser Ignition

Abstract: Laser ignition is a potential ignition technology to achieve reliable lean burn ignition in high brake mean effective pressure (BMEP) internal combustion engines. The technology has the potential to increase brake thermal efficiency and reduce exhaust emissions. This submission reports on engine testing of a Caterpillar G3516C stationary natural gas fueled engine with three types of ignition approaches: i) non-fueled electric prechamber plug with electrodes at the base of the prechamber (i.e., conventional ign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…LI systems are potentially attractive in this regard, for example, when applied to industrial reciprocating natural gas engines, LI has shown reduction in NO x emissions and extension of the lean limit 1 3 . The technology is of interest to a variety of combustion applications including reciprocating engines, aero-turbines, and rocket engines 4 – 10 . System level features of LI, as contrasted to conventional igniter technology, include: the lack of electrodes (which tend to act as heat sinks) within the combustion chamber, the ability to achieve fine control over ignition timing, flexibility in locating the ignition source (based on focusing optics), and potentially systems with favorable cost, packaging and reliability parameters.…”
Section: Introductionmentioning
confidence: 99%
“…LI systems are potentially attractive in this regard, for example, when applied to industrial reciprocating natural gas engines, LI has shown reduction in NO x emissions and extension of the lean limit 1 3 . The technology is of interest to a variety of combustion applications including reciprocating engines, aero-turbines, and rocket engines 4 – 10 . System level features of LI, as contrasted to conventional igniter technology, include: the lack of electrodes (which tend to act as heat sinks) within the combustion chamber, the ability to achieve fine control over ignition timing, flexibility in locating the ignition source (based on focusing optics), and potentially systems with favorable cost, packaging and reliability parameters.…”
Section: Introductionmentioning
confidence: 99%